PERBEDAAN HASIL EVALUASI PENGELOLAAN OBAT PUSKESMAS ISO DAN NON ISO KOTA SEMARANG TAHUN 2013 - Risha Fillah Fithria; Ika Desti Pratiwi (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2014)
ABSTRACTEmptiness and breakage of drugs in health centers often leads to non ISO patient dissatisfaction, which might be due to non optimal medication management. This study was conducted to determine the differences of the evaluation result of drug management between ISO and non ISO health centers in Semarang at 2013.This type of research is analytic survey, with a sample of three of most visits ISO and non-ISO health centers and non-ISO. Retrospective data collection techniques along with free interview directed to drug manager. Materials and research tools were card stock, report morbidity data (LB1), recipes, and the inventory check. Data were evaluated every month used the indicators of the Ministry of Health of Indonesia in 2010 and were analyzed used independent sample t test and Mann Whitney.The result showed that there was difference of the evaluation result of drug management between ISO and non ISO health centers in Semarang at 2013 on indicator of available drugs item complies with DOEN (t <1.66691) and the percentage of generic drugs writing (t <1.66691).Keywords : Drug Management, ISO Health Centers, Non ISO Health Centers, Semarang City